Effect of cyclic loading on bond strength of fiber posts to root canal dentin. - Zahra Khamverdi; Leila Yazdani Damavandi; Shahin Kasraei (Tehran University of Medical Sciences, 2014)
The aim of this study was to evaluate the effect of cyclic loading on the bond strength of quartz fiber posts to root canal dentin after different surface treatments of different regions of root canal dentin.Forty-eight single-rooted human teeth were selected. Post spaces were prepared and then the teeth were divided into four groups: G1: no treatment (control); G2: irrigation with a chemical solvent; G3: etching with 37% phosphoric acid; G4: treatment with ultrasonic file. The fiber posts were cemented using dual-cured resin cement. Half of the specimens were load-cycled (10000 cycles, 3 cycles/s) and the others did not undergo any load cycling. From each root, two slides measuring 1 mm in thickness were obtained from the apical and cervical regions. The push-out bond strength test was performed for each slice. Data were analyzed by using 3-way ANOVA and Tukey HSD tests. The fracture modes were evaluated under a stereomicroscope at ×20.The effect of load cycling and surface treatment as the main factors and the interaction of main factors were not significant (P=0.734, P=0.180, and P=0.539, respectively). The most frequent failure mode under the stereomicroscope was adhesive.It appears that load cycling and surface treatment methods had no effect on the bond strength of fiber posts to root canal dentin, but it depended on the region of the root canal dentin.